2018
DOI: 10.1002/anie.201801452
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis with Pnictogen, Chalcogen, and Halogen Bonds

Abstract: Halogen‐ and chalcogen‐based σ‐hole interactions have recently received increased interest in non‐covalent organocatalysis. However, the closely related pnictogen bonds have been neglected. In this study, we introduce conceptually simple, neutral, and monodentate pnictogen‐bonding catalysts. Solution and in silico binding studies, together with high catalytic activity in chloride abstraction reactions, yield compelling evidence for operational pnictogen bonds. The depth of the σ holes is easily varied with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
270
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(290 citation statements)
references
References 74 publications
4
270
0
16
Order By: Relevance
“…In XB organocatalysis, neutral molecule activation has mostly been achieved with iodine‐based catalysts, and the heavier chalcogens are similarly known to produce stronger noncovalent Lewis acids (Te>Se>S) . Interestingly, previous ChB catalysts were mostly based on S and Se, with the very few examples of Te‐based catalysts being restricted to neutral compounds or derivatives in which the Te substituent is bound to a neutral moiety (in an overall monocationic compound) . In this study, we decided to focus on dicationic bidentate selenium‐ and especially tellurium‐based compounds, to achieve maximum Lewis acidity.…”
Section: Methodsmentioning
confidence: 99%
“…In XB organocatalysis, neutral molecule activation has mostly been achieved with iodine‐based catalysts, and the heavier chalcogens are similarly known to produce stronger noncovalent Lewis acids (Te>Se>S) . Interestingly, previous ChB catalysts were mostly based on S and Se, with the very few examples of Te‐based catalysts being restricted to neutral compounds or derivatives in which the Te substituent is bound to a neutral moiety (in an overall monocationic compound) . In this study, we decided to focus on dicationic bidentate selenium‐ and especially tellurium‐based compounds, to achieve maximum Lewis acidity.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the large number of theoretical studies that have been disclosed, experimental investigations on pnictogen bonding are mainly limited to single‐crystal X‐ray studies . Notably, only a few spectroscopic investigations have been reported even though methods such as NMR spectroscopy are ideally suited for gaining fundamental understanding of pnictogen bonding. However, minor changes in chemical shifts may only be expected due to the weak nature of these interactions.…”
Section: Methodsmentioning
confidence: 99%
“…It is interesting to note that the Lewis acidity at antimony can also be imparted through the use of perfluorinated ligands.W hile SbPh 3 (1)d oes not possess any notable Lewis acidity,M atile et al have shown recently that Sb(C 6 F 5 ) 3 (2) binds chloride anions and catalyzes reactions involving organic chlorides ( Figure 1). [10] Thea ffinity that 2 displays for the chloride anion again illustrates the presence of al ow lying s*o rbital that accepts al one pair from the incoming halide.T his phenomenon can also be referred to as resulting from the presence of aso-called s-hole, [11] aterm that usually emphasizes the contribution of electrostatic forces to the interaction ( Figure 2). [12] Herein, we show that oxidation of antimony to the + Vs tate can be used to carve the electrostatic potential profile about the antimony atom, leading to ad eeper s-hole.W ea lso demonstrate that control over the depth of the s-hole impacts the affinity of antimony for incoming electron-rich substrates and turns on catalysis.…”
mentioning
confidence: 94%